Epithetisation lndicator in Stylistic Research - Ruszkowski, Marek (Respectus Philologicus, 2004)
This article attempts to analyse the main parts of speech (noun, verb, adjective and adverb) and their quantitative proportion in various types of texts. The quantitative relations among the main parts of speech are one of the statistical characterisations of the text. Epithetisation Indicator (EI), which is calculated by dividing the sum of the nouns used by the sum of the used adjectives, is important to define the stylistic quality of the text. The higher the value, the lower the degree of epithetisation because this indicator shows how many nouns can be assigned to one adjective on average. The degree of epithetisation belongs to those features of the text, which can be expressed in numbers. The value of the analysed parameter is of prime importance to determine the stylistic properties of the text and the register level (informal - semiformal - formal). It may characterise both the style of particular texts, writers, literary genres and the functional styles. Moreover, it may suggest the age of a person whose discourse is being analysed. Any deviation from the EI mean value is always stylistically relevant. However, Epithetisation Indicator is only one of many tools to be used in the stylistic analysis and interpretation of the text by means of qualitative methods. The comparison of various values of the analysed parameter shows that the style of the text may be defined by means of purely statistical terms but this characterisation should be supplementary to the qualitative description.